2018
DOI: 10.1111/nyas.13867
|View full text |Cite
|
Sign up to set email alerts
|

From multisensory integration in peripersonal space to bodily self‐consciousness: from statistical regularities to statistical inference

Abstract: Integrating information across sensory systems is a critical step toward building a cohesive representation of the environment and one's body, and as illustrated by numerous illusions, scaffolds subjective experience of the world and self. In the last years, classic principles of multisensory integration elucidated in the subcortex have been translated into the language of statistical inference understood by the neocortical mantle. Most importantly, a mechanistic systems-level description of multisensory compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 224 publications
(382 reference statements)
5
49
0
Order By: Relevance
“…Indeed, a main interest here resided in the putative impact that the presence or absence of a visual depiction of a virtual hand may have on the underlying visuo-proprioceptive coupling prior. In fact, we suggest that PPS can be conceived to be a ‘stochastic bubble’ surrounding the body and computing the probability that an object will come in contact with the body (see 56 for similar arguments). As such, in principle, the measurement of the strength of the link between body-related information (i.e., proprioceptive signals) and surrounding exteroceptive signals (i.e., visual) arguably provides an index for the computation of proximity to the body that may characterize the functionality of PPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a main interest here resided in the putative impact that the presence or absence of a visual depiction of a virtual hand may have on the underlying visuo-proprioceptive coupling prior. In fact, we suggest that PPS can be conceived to be a ‘stochastic bubble’ surrounding the body and computing the probability that an object will come in contact with the body (see 56 for similar arguments). As such, in principle, the measurement of the strength of the link between body-related information (i.e., proprioceptive signals) and surrounding exteroceptive signals (i.e., visual) arguably provides an index for the computation of proximity to the body that may characterize the functionality of PPS.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Guterstam and colleagues suggest that the “magnetic touch illusion” is a perceptual correlate of visuo-tactile integration in the PPS 54 , and taken together, these results imply that the PPS allows for the inference of putative touch by nearby objects. In turn, aiming to develop a computational framework accounting for the functional role of PPS, here we argue that PPS can be conceived as a “stochastic spatial bubble” surrounding the body wherein the probability that objects in the world could come into contact with the body is computed (see 44 , 48 , 49 , 51 , 56 , 57 for similar arguments). Arguably, the PPS may allow for the computation of the probability that sensory signals are associated with each other and most importantly with one’s body.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, contact-related behavioural relevance also explains the relationship between many PPS measures and impact prediction 15 , 73 , 74 : the probability of impact of a stimulus is strongly related to the behavioural relevance of an action aiming to avoid or create contact [9] . Interestingly, recent views have suggested that impact prediction is the main role of PPS [75] . While such a role does explain that some factors other than proximity (e.g., velocity or direction of movement) affect PPS measures, it still does not explain, for example, the effect of other factors, such as stimulus valence [14] , lateral motion [7] (i.e., in a direction not likely to directly cause impact with the individual), and social interactions [76] , factors that are instead explained by considering contact-related action relevance.…”
Section: Pps As a Set Of Contact-related Action Fieldsmentioning
confidence: 99%
“…In the Control group a non-significant difference between RTs at D4 (M = 1017.11, SE = 16.71) and D5 (M = 998.71, SE = 13.03) was found, (t (16) = 1.87, p = .079), whereas RTs at D3 (M = 1061.39, SE = 17.86) were slower than at D4 (t (16) = 2.91, p = .010), RTs at D2 (M = 1100.99, SE = 20.28) were slower than RTs at D3 (t (16) = 4.46, p < .001) and RTs at D1 (M = 1170.56, SE = 30.50) were slower than RTs at D2 (t (16) = 3.78, p = .002). Interestingly, in the pregnant group, t-tests showed a non-significant difference between RTs at D4 (M = 1045.76, SE = 11.59) and D5 (M = 1031.99, SE = 10.27), (t (27) = 1.78, p = .085) and between RTs at D3 (M = 1050.25, SE = 11.81) and D4, (t (27) = .56, p = .576), whereas RTs at D2 (M = 1101.70, SE = 11.86) were slower than RTs at D3 (t (27) = 7.69, p < .001), and RTs at D1 (M = 1131.50, SE = 13.32) were slower than RTs at D2 (t (27) = 2.88, p = .008). See Figure 1 (graph "b").…”
Section: Resultsmentioning
confidence: 96%
“…The shallower slope of the PPS gradient observed at the late stage of pregnancy seems therefore to indicate a weaker and more variable sense of body boundary, perhaps caused by the inability of the brain to accurately keep track of the fast body changes. Interestingly, the PPS has been defined as a "stochastic bubble" where computations about the probability of the body interacting with external objects continuously occur 27 . The wider margin of the "safety zone" around the body observed late in pregnancy could be a consequence of the brain's reduced ability to accurately compute the exact spatial location of an external stimulus with respect to one's ownrapidly growing -body.…”
Section: Discussionmentioning
confidence: 99%